Peer-to-peer groups learning from those you trust - Schell, Jim (Lights On Publishing, 2017)
"A peer-to-peer group made up of people with similar interests can be the premier learning tool of them all if structured correctly. And who better to learn from than group members who have already learned life’s lessons the hard way? In Peer-to-Peer Groups: Learning from Those You Trust you’ll learn how to create and facilitate a collaborative and caring team of peers; the long list of beneﬁts that peer-to-peer teams provide to their participants; the three core values that every peer-to-peer team must have; how to vet and recognize the members that will best ﬁt your team; the keys to becoming a crackerjack facilitator of all meetings, peer-to-peer and otherwise; the many tricks required to make a team meeting click; developing an agenda that works for everyone; [and] the difference peer-to-peer teams can make in your community" -- provided by publisher
Keywords: Teams in the workplace; Social groups; Group facilitation; Mentoring